Electroactive Covalent Organic Frameworks: Design, Synthesis, and Applications. Issue 44 (8th July 2020) - Yusran, Yusran; Fang, Qianrong; Valtchev, Valentin
Abstract: Covalent organic frameworks (COFs) are an emerging class of crystalline porous polymers with tailorable compositions, porosities, functionalities, and intrinsic chemical stability. The incorporation of electroactive moieties in the structure transforms COFs into electroactive materials with great potential for energy‐related applications. Herein, the recent advances in the design and use of electroactive COFs as capacitors, batteries, conductors, fuel cells, water‐splitting, and electrocatalysis are addressed. Their remarkable performance is discussed and compared with other porous materials; hence, perspectives in the development of electroactive COFs are presented. Abstract : The design of electroactive covalent organic frameworks (COFs) is addressed. Their performance as capacitors, batteries, conductors, fuel‐cells, and electrocatalysts is compared with that of other porous materials. Perspectives for electroactive COFs in these new advanced applications are provided.